1993
DOI: 10.1182/blood.v81.11.3097.3097
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of Hodgkin and Reed-Sternberg cells: molecular heterogeneity of gene expression and p53 mutations

Abstract: We have used a single-cell based polymerase chain reaction (PCR) amplification technique to examine the gene expression pattern in single Hodgkin's and Reed-Sternberg (H&RS) cells from seven patients with Hodgkin's disease. Single cells were isolated from lymph nodes obtained at diagnosis (5 of 7 patients) or in first or second relapse (2 of 7 patients). Gene expression was examined by hybridization to a panel of 22 cDNA probes. Forty-nine H&RS cells (and 23 CD3+ or CD20+ lymphocytes as controls) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(36 citation statements)
references
References 41 publications
(3 reference statements)
1
34
0
1
Order By: Relevance
“…Myelodysplastic syndrome. The myelodysplastic syndrome (MDS) cohort of patients included subtypes: refractory anemia with excess of blasts (RAEB), refractory anemia with excess of blasts in transformation (RAEB-T), and a single patient with chronic 1993; Cesarman et al, 1993;Lo Coco et al, 1993;O'Connor et al, 1993;Gaidano et al, 1993;Nakamura et al, 1993;Bhatia et al, 1993;Villuendas et al, 1993;Trumper et al, 1993;Ballerini et al, 1993;Baldini et al, 1994;Farrugia et al, 1994;Watanabe et al, 1994;Chang et al, 1994;De Re et al, 1994;Matolcsy et al, 1994;Matsushima et al, 1994;Edwards et al, 1994;Koga et al, 1994;Preudhomme et al, 1995;Kocialkowski et al, 1995;Knowles et al, 1995;Louie et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Myelodysplastic syndrome. The myelodysplastic syndrome (MDS) cohort of patients included subtypes: refractory anemia with excess of blasts (RAEB), refractory anemia with excess of blasts in transformation (RAEB-T), and a single patient with chronic 1993; Cesarman et al, 1993;Lo Coco et al, 1993;O'Connor et al, 1993;Gaidano et al, 1993;Nakamura et al, 1993;Bhatia et al, 1993;Villuendas et al, 1993;Trumper et al, 1993;Ballerini et al, 1993;Baldini et al, 1994;Farrugia et al, 1994;Watanabe et al, 1994;Chang et al, 1994;De Re et al, 1994;Matolcsy et al, 1994;Matsushima et al, 1994;Edwards et al, 1994;Koga et al, 1994;Preudhomme et al, 1995;Kocialkowski et al, 1995;Knowles et al, 1995;Louie et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The p53 gene has been investigated in HD in several studies (28,45,56,57). Most of these have shown that H-RS cells frequently express p53 protein, but that point mutations are absent or rare (56 (17) studied p53 by singlecell PCR and demonstrated identical point mutations in exon 7 in five of seven H-RS cells isolated from one of seven HD cases. Chen et al ( 1996) (12) isolated areas rich in H-RS cells by micromanipulation and demonstrated that point mutations in exons 6 to 8 could be identified in 6 of 23 cases.…”
Section: Attactactactact Acggtatggacgtct G G G G C C a A G G G~ Fggtcmentioning
confidence: 99%
“…These results have been obtained by analysis of crude extracts of genomic DNA from tissue specimens in which the H-RS cells only constitute a small minority. More recently, different approaches have been taken by Trumper et al( 1993) ( 17) and Chen et al( 1996) ( 12) Trumper et al (1993).…”
mentioning
confidence: 99%
“…In Hodgkins disease, P53 mutations may be confined to Reed-Sternberg cells in many cases (Gupta et al, 1993a, b). Because those cells only constitute a small part of the cell infiltrate, P53 may not be recognized by conventional methods (SSCP, ICC, IHC) without prior enrichment of the Reed-Sternberg cell population Trumper et al, 1993).…”
Section: Incidence and Type Of P53 Mutations In Haematological Malignmentioning
confidence: 99%